The Current Approaches to the Formation of Marketing Tools of Enterprise Management - Raiko Diana V.; Podrez Olha I.; Cherepanova Viktoriia О. (Problemi Ekonomiki, 2022)
The purpose of the article is to clarify the theoretical principles of the formation and application of marketing tools, determine their place in the enterprise management system, classification by type of marketing activities and distribution into traditional and novel ones. Management tools play an important role in fulfilling the mission and achieving the goals that are set for an enterprise, since they represent the ways, means, techniques for the specific implementation of the goals of managing a business entity. Marketing tools are the basis of the efficiency of marketing activities of the enterprise. In the article, marketing tools are divided into three groups: by type of marketing research; by the marketing complex; by analyzing the effectiveness and efficiency of marketing activities. It is proposed to form the third group of tools according to three directions – evaluation of the use of the marketing complex from the standpoint of its activity, effectiveness and efficiency of marketing activities, and its impact on the level of social responsibility of the enterprise. Each group contains both traditional tools covering traditional research methods, elements and policies of marketing, as well as the novel ones, which are based on modern information technologies, psychological techniques, economic-mathematical models and methods